Relationship of the Esophageal Microbiome and Tissue Gene Expression and Links to the Oral Microbiome: A Randomized Clinical Trial. Issue 12 (7th December 2020) - Annavajhala, Medini K.; May, Michael; Compres, Griselda; Freedberg, Daniel E.; Graham, Roseanna; Stump, Stephania; Que, Jianwen; Korem, Tal; Uhlemann, Anne-Catrin; Abrams, Julian A.
Abstract : INTRODUCTION: Although the microbiome is altered in various esophageal diseases, there is no direct evidence for a link between the oral or esophageal microbiome and underlying esophageal tissue. Here, we aimed to address these gaps through use of an antimicrobial mouth rinse to modify the esophageal microbiome and tissue gene expression. METHODS: In this randomized controlled trial, patients scheduled to undergo endoscopy for clinical indications used chlorhexidine mouth rinse or no treatment for 2 weeks before endoscopy. Oral swabs and saliva were collected at baseline and at follow-up, and the esophagus was sampled on the day of endoscopy. The microbiome was analyzed by 16S rRNA gene sequencing, and esophageal tissue gene expression was ascertained by RNA-Seq. RESULTS: Twenty subjects were enrolled and included in the analyses. Within individuals, the oral and esophageal microbiome composition was significantly correlated. Chlorhexidine treatment associated with significant alterations to the relative abundance of several esophageal bacterial taxa, and to expression of genes in the esophagus including reductions in periostin, claudin-18, chemokines CXCL1 and CXCL13, and several members of the tumor necrosis factor receptor superfamily. A taxon in genus Haemophilus in the esophagus also associated with significant changes in tissue gene expression. DISCUSSION: The oral and esophageal microbiomes are closely related within individuals, and esophageal microbiome alterations correlate with tissue gene expression changes. The esophageal microbiome may act as an important cofactor that influences pathogenesis and outcomes of diseases such as eosinophilic esophagitis, gastroesophageal reflux, and Barrett's esophagus.